Combating political and bureaucratic corruption in Uganda: Colossal challenges for the church and the citizens - Asea, Wilson B. (AOSIS, 2018)
This article formulates a new approach to combating corruption in Uganda. In pursuit of this research, the author highlights the chronicity of corruption in Uganda, which is uniformly political and bureaucratic. Bureaucratic corruption takes place in service delivery and rule enforcement. It has two sides: demand-induced and supply-induced. Political corruption occurs at high levels of politics. There are ‘political untouchables’ and businessmen who are above the law and above institutional control mechanisms. The established institutions of checks and balances in Uganda have assiduously continued to have a limited bearing on corruption. Neither coherent anti-corruption norms nor severe formal sanctions are able to dishearten certain politicians and civil servants in Uganda from the deviant behaviour of structural corruption. Corruption is a spiritual departure from the law and standard of God. It is an action conceived in the human mind and carried out by the corrupt. Therefore, corruption deterrence not only lies in sound public financial management systems but depends to a large extent on having people with positive human character in all aspects of national life. This article thus provides the framework of corruption and discusses the manifestation of political and bureaucratic corruption in Uganda. It also exegetes the biblical stance regarding corruption. Finally, it proposes a panacea for combating political and bureaucratic corruption.